Short-Term Creep Experiment of Cement Asphalt Mortar and Its Numerical Simulation - Hao Xu; Ping Wang; Hong-song Lin; Hua Yan (Advances in Materials Science and Engineering)
In order to investigate the creep performance of cement asphalt mortar (CA mortar), the field sampling of CA mortar cylinder samples was produced, and all samples were tested on WDW series electric universal testing machine by using uniaxial static creep test at 25°C, and the load stress levels were 0.05 MPa, 0.1 MPa, 0.3 MPa, and 0.5 MPa. The greater the load is, the bigger the creep deformation is. The creep performance was simulated by using Burgers model, and the correlation coefficients between fitting results of Burgers model and experimental results are all greater than 0.9. Based on the requirements of finite element software, the Prony series of Burgers model was obtained, and the short-term creep process of CA mortar was simulated by the finite element software ANSYS. The relative error between simulation results and experimental data is not more than 2.5%, which indicates that the short-creep process of CA mortar can be simulated by ANSYS software. The study results can improve the structural design theory of slab track.